КЎП МАЪНОЛИ СЎЗ ВА УНИНГ ЎРГАНИЛИШИ ХУСУСИДА - Гулямова, Ш.К. (SCIENCE and SOCIETY, 2020)
This article discusses in detail the phenomenon that has existed in linguistics since ancient times-the peculiarity of polysemy, its application, its relation with the accompanying phenomenon – homonymy. The attitude of scientists to the polysemous word is expressed and generalized. The fact that some linguists do not recognize the phenomenon of polysemy, based on the fact that it is not justified, on the contrary, many relevant words are synonyms, for example the antonym and the homonym, the development of language, its richness, its ability to integrate many values in one word, an obvious manifestation of principles of economy in language.